Influence of Leptin and Adiponectin Supplementation on Intraepithelial Lymphocyte and Microbiota Composition in Suckling Rats - Grases-Pintó, Blanca; Abril-Gil, Mar; Castell, Margarida; Rodríguez-Lagunas, Maria J.; Burleigh, Stephen; Fåk Hållenius, Frida; Prykhodko, Olena; Pérez-Cano, Francisco J.; Franch, Àngels (Frontiers in Immunology, 2019)
Dietary components in early life play a role in both microbiota and intestinal immune system maturation in mammalian species. Adipokines, as endogenously produced hormones from breast milk, may have an impact on this process. The aim of the present study was to establish the influence of leptin and adiponectin supplementation during suckling on the intraepithelial lymphocyte composition, intestinal barrier function, intestinal gene expression and gut microbiota in rat. For this purpose, newborn Wistar rats were supplemented daily with leptin, adiponectin or whey protein concentrate during the first 21 days of life. Lymphocyte composition was established by immunofluorescence staining and flow cytometry analysis; intestinal gene expression by real-time PCR and cecal microbiota were analyzed through 16S rRNA gene sequencing. Although leptin and adiponectin were able to increase the Tc TCRαβ+ and NKT cell proportion, they decreased the NK cell percentage in IEL. Moreover, adipokine supplementation differentially modified CD8+ IEL. While the supplementation of leptin increased the proportion of CD8αα+ IEL (associated to a more intestinal phenotype), adiponectin enhanced that of CD8αβ+ (related to a peripheral phenotype). Furthermore, both adipokines enhanced the gene expression of TNF-α, MUC-2 and MUC-3, and decreased that of FcRn. In addition, the adipokine supplementations decreased the abundance of the Proteobacteria phylum and the presence of Blautia. Moreover, leptin-supplemented animals had lower relative abundance of Sutterella and a higher proportion of Clostridium genus, among others. However, supplementation with adiponectin resulted in lower abundance of the Roseburia genus and a higher proportion of the Enterococcus genus. In conclusion, the supplementation with leptin and adiponectin throughout the suckling period had an impact on both the IEL composition and the gut microbiota pattern, suggesting a modulatory role of these adipokines on the development of intestinal functionality.